A MODEL TO INCREASE INSTRUCTOR’S RESPONSIVENESS IN A MOOC COURSE BY AUTOMATING REPLIES TO THE LEARNERS’ QUERIES - Mallika Vijayakumar, Surendheran Kaliyaperumal (International Journal of Advanced Science and Technology, 2020)
Soon after the invention of the World Wide Web, the face of communication has received remarkable improvements. Due to the rapid growth in the field of computer science, many sectors have been given the ability to adapt to future needs in the field of education also had its share. The concept of massive open online courses (MOOCs) is a breakthrough in distance education sector. MOOC allows the learners and instructors to make use of the flexibility derived from the Internet, multimedia and advanced electronic hardware to create and deliver quality learning content no matter how far they instructor and the learners are located. As every coin has its other side, MOOCs as several shortcomings and is far from perfection at the moment. Learners’ retention rate with a course is highlighted as one of its major shortcomings by several kinds of research. According to a few studies, the quality of the communication between the instructor and the learners is being pointed out as one of the predictors of learners’ retention rate. The authors of this article are proposing a model to automate the communication from the instructor to a certain level which may in return increase the quality of the communication and the frequency of the instructors’ response. The authors suggest that this model might have a positive impact on learner’s continuity with the course due to the increased activity of the instructor.